2013
DOI: 10.1159/000354235
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid Increases Medial Calcification by Inducing Oxidative Stress

Abstract: Background: Aortic medial calcification is a cellular-regulated process leading to arterial stiffness. Although epidemiological studies have suggested an association between the saturation of fatty acids (FA) and arterial stiffness, there is no evidence that saturated FA can induce arterial calcification. This study investigated the capacity of palmitic acid (PA) to induce medial calcification and the signaling pathway(s) implicated in this process. Methods: Rat aortic segments and vascular smooth muscle cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 85 publications
2
33
0
Order By: Relevance
“…Cholesterol and oxysterols could cause mitochondria dysfunction and ROS production 3, 4 . Saturated fatty acids, but not unsaturated fatty acids, also efficiently induce ROS generation through activating NADPH oxidation and mitochondrial electron transport 5, 6 . However, how cells sense and adapt to lipid overload-induced oxidative stress remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol and oxysterols could cause mitochondria dysfunction and ROS production 3, 4 . Saturated fatty acids, but not unsaturated fatty acids, also efficiently induce ROS generation through activating NADPH oxidation and mitochondrial electron transport 5, 6 . However, how cells sense and adapt to lipid overload-induced oxidative stress remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential mechanisms are not clear. Although Brodeur et al found that downregulating the osteogenic mRNA expression of cbfa1, alkaline phosphatase and osteocalcin was associated with the beneficial effects of apocynin on VC [27], the mechanisms between apocynin and VSMCs phenotypic switching have not been further explored. In this work, we paid more attention to how apocynin affected VSMCs switching from a contractile to osteogenic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…3). It has been previously suggested that the unsaturated fatty acid stearate [12,39] and -to a lesser extentpalmitate [39,40] can induce calcification in vascular smooth muscle cells. However, this is not the case with monounsaturated 18C chains, which have been previously shown to demonstrate the opposite or no effect [12].…”
Section: Dysregulated Processes In Severe Ccadmentioning
confidence: 99%